Easily Conducted Tests During the First Week Post-stroke Can Aid the Prediction of Arm Functioning at 6 Months - Ghaziani, Emma; Couppé, Christian; Siersma, Volkert; Christensen, Hanne; Magnusson, S. Peter; Sunnerhagen, Katharina S.; Persson, Hanna C.; Alt Murphy, Margit (Frontiers in Neurology, 2020)
Background: Prognostic models can estimate the recovery of arm functioning after stroke, guide the selection of individual training strategies, and inform patient selection in clinical trials. Several models for early prediction of arm recovery have been proposed, but their implementation has been hindered by insufficient external validation, limited evidence of their impact on patient outcomes, and reliance on predictors that are not feasible in regular clinical practice. Objectives: To determine the predictive value of new and previously reported tests that can be easily conducted in regular clinical settings for early prognosis of two levels of favourable arm recovery at 6 months post-stroke. Methods: We performed a secondary analysis of merged data (n=223) from two Scandinavian prospective longitudinal cohorts. The candidate predictors were seven individual tests of motor function and the sensory function measured by the Fugl-Meyer Assessment of Upper Extremity within 7 days post-stroke, and the whole motor section of this assessment. For each candidate predictor, we calculated the adjusted odds ratio (OR) of two levels of residual motor impairment in the affected arm at 6 months post-stroke: moderate (≥32 points on the motor section of the Fugl-Meyer Assessment of Upper Extremity, FMA-UE) and mild (FMA-UE≥58 points). Results: Patients with partial shoulder abduction (OR 14.6), elbow extension (OR 15.9) and finger extension (OR: 9.5) were more likely to reach FMA-UE≥32. Patients with full function on all individual motor tests (OR 5.5-35.3) or partial elbow extension, pronation/supination, wrist dorsiflexion and grasping ability (OR 2.1-18.3) were more likely to achieve FMA-UE≥58 compared with those with absent function. Intact sensory function (OR 2.0-2.2) and moderate-to-mild motor impairment on the FMA-UE (OR 7.5) were also associated with favourable outcome. Conclusions: Easily conducted motor tests can be useful for early prediction of arm recovery. The added value of this study is the prediction of two levels of a favourable functional outcome from simple motor tests. This knowledge can be used in the development of prognostic models feasible in regular clinical settings, inform patient selection and stratification in future trials, and guide clinicians in the selection of individualized training strategies for improving arm functioning after stroke.